Morphological landscapes from high content imaging reveal cytokine priming strategies that enhance mesenchymal stromal cell immunosuppression. Issue 2 (17th November 2021) - Andrews, Seth H.; Klinker, Matthew W.; Bauer, Steven R.; Marklein, Ross A.
Abstract: Successful clinical translation of mesenchymal stromal cell (MSC) products has not been achieved in the United States and may be in large part due to MSC functional heterogeneity. Efforts have been made to identify "priming" conditions that produce MSCs with consistent immunomodulatory function; however, challenges remain with predicting and understanding how priming impacts MSC behavior. The purpose of this study was to develop a high throughput, image‐based approach to assess MSC morphology in response to combinatorial priming treatments and establish morphological profiling as an effective approach to screen the effect of manufacturing changes (i.e., priming) on MSC immunomodulation. We characterized the morphological response of multiple MSC lines/passages to an array of Interferon‐gamma (IFN‐γ) and tumor necrosis factor‐⍺ (TNF‐⍺) priming conditions, as well as the effects of priming on MSC modulation of activated T cells and MSC secretome. Although considerable functional heterogeneity, in terms of T‐cell suppression, was observed between different MSC lines and at different passages, this heterogeneity was significantly reduced with combined IFN‐γ/TNF‐⍺ priming. The magnitude of this change correlated strongly with multiple morphological features and was also reflected by MSC secretion of immunomodulatory factors, for example, PGE2, ICAM‐1, and CXCL16. Overall, this study further demonstrates the ability of priming to enhance MSC function, as well as the ability of morphology to better understand MSC heterogeneity and predict changes in function due to manufacturing. Abstract : Andrews and colleagues develop a morphological screening platform to identify cytokine priming conditions that enhance mesenchymal stromal cell immunomodulatory function i.e. T cell suppression. Using this approach enabled identification of priming conditions that enhanced MSC suppression of T cells, as well as modulation of the MSC secretome relevant to this observed function.